Contextual moderators for leadership potential based on trait activation theory. (14th May 2019) - Luria, Gil; Kahana, Allon; Goldenberg, Judith; Noam, Yair
Summary: This study tested the moderating role of group properties in the relationship between two prototypical leadership attributes (cognitive ability and adjustment) and leadership potential. Building on trait activation theory, we investigated one organizational cue (degree of centralization in the informal social structure) and one social cue (average level of the relevant attribute among other group members) and posited that the two prototypical leadership attributes would more likely be activated (leading to leadership potential) in more centralized groups and in groups where others have lower levels of the studied attribute. We tested 874 combat soldiers undergoing basic training in 71 teams. In a time‐lagged design, we measured general cognitive ability and adjustment before conscription and then used regression analyses to calculate the group informal social structure and leadership potential several months after conscription. As predicted, the relationships of both adjustment and cognitive ability with leadership potential were moderated by group informal structure, with stronger relationships in groups with more centralized structures. Other group members' cognitive ability moderated the relationship between cognitive ability and leadership potential (stronger relationships in groups with lower mean of others' cognitive ability), but other group members' adjustment did not moderate the relationship between adjustment and leadership potential.